2007
DOI: 10.1038/sj.pcan.4500935
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of local anesthesia for transrectal ultrasound-guided biopsy of the prostate

Abstract: This meta-analysis evaluated the efficacy and safety of periprostatic nerve block (PPNB) and intrarectal local anesthestic (IRLA) gel in alleviating pain during prostate biopsy. Electronic databases MEDLINE, Cochrane Central Register of Controlled Trials and EMBASE were searched to identify all randomized controlled trials comparing PPNB with periprostatic placebo injection, no injection or with IRLA. Studies for inclusion were identified and extracted by two authors independently. The main outcome measure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 67 publications
4
58
1
Order By: Relevance
“…These results are supported by a meta-analysis of 6 studies with 872 patients comparing peri-prostatic nerve block to intra-rectal local anesthetic. 53 The authors reported a weighted mean difference of -1.53, 95% CI -2.67 to -0.39 (p=0.008), on a 10 point scale in favor of peri-prostatic nerve block over intra-rectal local anesthetic.…”
Section: Peri-prostatic Nerve Blockmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are supported by a meta-analysis of 6 studies with 872 patients comparing peri-prostatic nerve block to intra-rectal local anesthetic. 53 The authors reported a weighted mean difference of -1.53, 95% CI -2.67 to -0.39 (p=0.008), on a 10 point scale in favor of peri-prostatic nerve block over intra-rectal local anesthetic.…”
Section: Peri-prostatic Nerve Blockmentioning
confidence: 99%
“…A recent meta-analysis involving 5 studies and 466 patients found the intrarectal local anesthetic provided better pain relief then no anesthetic or placebo, but the weighted mean difference between the groups did not reach statistical significance. 53 Other studies have suggested that intra-rectal local anesthetic alone is not sufficient for pain relief during the biopsy procedure. 59 Although it works well to reduce the pain associated with probe insertion it does not address the pain associated with injection of the prostate capsule.…”
Section: Intra-rectal Local Anestheticmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 A systematic review relating to urological surgery analyzed pain scores and other secondary outcomes without looking for mortality in the context of the choice of anesthetic technique. 1,3 In this context, we conducted a study to answer one research question: what is the difference in mortality rate between using general anesthesia and using neuraxial anesthesia for urological surgery?…”
Section: Introductionmentioning
confidence: 99%